HLA-DRB1 polymorphism in recurrent pregnancy loss: New evidence for an association to HLA-DRB1*07. (June 2021) - Thomsen, C.K.; Steffensen, R.; Nielsen, H.S.; Kolte, A.M.; Krog, M.C.; Egerup, P.; Larsen, E.C.; Hviid, T.V.; Christiansen, O.B.
Highlights: The HLA-DRB1*07 allele frequency is increased in recurrent pregnancy loss women. Homozygocity for the allele is associated with recurrent pregnancy loss (OR 2.27). The HLA-DRB1*03 allele was not associated with recurrent pregnancy loss. Abstract: Many cases of recurrent pregnancy loss (RPL) defined as ≥3 consecutive pregnancy losses are suggested to be caused by an aberrant maternal immune response against the fetus or trophoblast. Human leukocyte antigen (HLA)–DRB1 and -DQB1 polymorphisms are associated with most autoimmune disorders and studies of HLA-DBB1 polymorphism in RPL patients are thus relevant. In previous studies, the HLA-DRB1*03 allele was found with increased prevalence in RPL patients. We wanted to clarify whether HLA-DRB1 alleles indeed were associated with RPL among women of Caucasian descent. A total of 1078 women with unexplained RPL and 2066 bone marrow donors were HLA-DRB1-typed and subsets were also HLA-DQB1 typed. All patients were initially HLA-DRB1-typed by DNA-based low-resolution techniques and subsets of patients and all controls were typed by high-resolution techniques. Among patients, the HLA-DRB1*07 allele frequency was significantly increased compared with controls; OR 1.29 (95 % CI 1.09−1.52), p < 0.0025; after correction for multiple comparisons pc = 0.031. The HLA-DRB1*07/*07 genotype was highly increased in patients with RPL compared with controls: OR 2.27 (1.31−3.93), p = 0.0027. The frequency of the HLA-DRB1*07 phenotype in RPL patients had increased significantly (p = 0.002) in three studies from our group published 1994–2021. The allele frequency of HLA-DRB1*03 was not increased in RPL patients compared with controls; OR 0.96 (0.83−1.12). In conclusion, the previous association between HLA-DRB1*03 and RPL could not be confirmed in our study whereas an association to HLA-DRB1*07 was detected for the first time. Since the latter association is a new finding, it should be confirmed in future studies.